Evaluation of the Coupling and Coordination Relationships between Economic Growth and the Ecological Environment in Qinghai Province - Lian, Enhui; Qi, Dengju; Hu, Xiwu (Journal of Theory and Practice in Economics and Management, 2025)
Qinghai Province shoulders the important task of maintaining national ecological security. To promote the construction of an "ecological civilization pilot zone", it is necessary to coordinate the economic growth and ecological environment of the province. This paper uses panel data from 2008--2018 to construct an indicator system from the two dimensions of economic growth and ecological protection and uses the entropy method and coupling coordination model to measure and evaluate the development level of Qinghai Province's economy and ecological protection. The results show that (1) from 2008–2018, the changes in the coupling degree and coupling coordination degree of the two systems of economic growth and ecological protection in Qinghai Province basically showed a steady upward trend. (2) From 2008--2015, the degree of economic‒eco-ecological coupling was in the antagonistic stage, and the degree of coupling coordination tended to change from moderate to mild. (3) From 2016 to 2018, the degree of coupling was in the running-in stage, the degree of coupling coordination was stable under mild imbalance, and there was a trend toward near-disharmony and coordinated development, indicating that the coordinated development level of the economy and ecology has moved toward coordinated development.